The Physical Integration of Smart Transportation Characteristics of Suroboyo Bus and the Feeder - Cindy Nur Aziza Rahman; Eko Budi Santoso; Siti Nurlaela (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Surabaya City is one of the cities in Indonesia that applies smart mobility. In implementing smart transportation, Surabaya city has already had a mode of transportation that supports the implementation of the ITS-ATCS infrastructure, namely Surabaya Bus. Not only to rely on advanced transportation modes and infrastructure facilities, one of the principles of smart transportation is the integration of modes. This study aims to examine the characteristics of physical integration that can be developed and maximized for the application of the Suroboyo bus multimodal smart transportation integration. The research method uses for the analysis is descriptive analysis while the method used for the data collection is primary data collection. The physical integration of smart transportation characteristics of Suroboyo Bus and the feeder such as the use of terminals, the use of bus stops, and transfers, need to maximize their function in the application of the physical integration of smart transportation for Suroboyo bus and feeder transportation.